Increasing The Capacity of Posyandu Cadres in Implementing Posyandu Activities in Bunijaya, Jatisari Village, Kutawaringin District, Bandung Regency - Yanti Setiawati; Wasifah Hanim (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The role of posyandu cadres in increasing awareness and understanding of mothers and toddlers on the importance of posyandu activities is enormous, especially in monitoring and growing toddlers and pregnant/breastfeeding women. One of the problems faced by Posyandu cadres in Kampung Bunijaya Rw.11 Jatisari Village, Kutawaringin District, is a lack of understanding in determining whether children are experiencing good nutrition or malnutrition and procedures for providing posyandu activities because these cadres are new cadre members. This activity aims to improve the quality of Posyandu services. The method used in this activity is socialization by providing counseling and assistance in the service of Posyandu activities. Providing counseling on preparing additional food menus to improve toddler nutrition will offer new insights into monitoring child growth and development through KMS and assist in carrying out posyandu activities that are orderly and regular. The result of this activity is an increase in the capacity of cadres to provide posyandu activities to the community and increasing the role of the posyandu as the spearhead of more optimal monitoring of maternal and child health.